INFLUENCE OF FOLIAR FEEDING WITH BIOLOGICALLY ACTIVE SUBSTANCES ON THE GRAIN AND GREEN MASS YIELD OF SUNFLOWER - B.U, Suvanov; Yu.S, Suvonova (Research Focus International Scientific Journal, 2026)
This article examines the effect of foliar feeding with biologically active substances on the duration of the growing period, morphological characteristics, and grain yield of the sunflower cultivar “Jahongir”. The experiments used the preparations “Xumuz baraka” “BioDeposit”, and “Biomex-kemi”, while an untreated variant served as the control. The results showed that the variant treated with “Biomex-kemi” had a shorter growing period and the highest plant height, number of leaves, head morphological characteristics, and grain yield. The grain yield in this variant reached 3.23 t/ha. The study demonstrated that foliar feeding with biologically active substances, especially “Biomex-kemi”, is effective for obtaining a high and high-quality yield from the sunflower cultivar “Jahongir”.